Assessment of Flexion Elongation Relation and Type of Failure after Capsulodesis - Bakker, Daniel; Kraan, Gerald A.; Mathijssen, Nina M. C.; Colaris, Joost W.; Kleinrensink, Gert-Jan (Journal of Wrist Surgery, 2020)
Background Injury of the scapholunate interosseous ligament is the most frequently diagnosed cause of carpal instability and can be treated with a Mayo capsulodesis procedure. During this procedure, a radially based flap of the dorsal radiocarpal complex is attached to the lunate. The procedure attempts to reduce flexion of the scaphoid and restore the scapholunate relationship by crossing the scapholunate interval. To obtain a better understanding of the biomechanical properties and possibly improve the postoperative rehabilitation process, a better understanding of the reconstructions biomechanics is needed.Methods Ten dorsal intercarpal ligament capsulodesis were performed on embalmed wrists to assess the flexion elongation relation at the dorsal intercarpal reconstruction, the dorsal intercarpal complex, and the type of failure during flexion of the wrist.Results The mean elongation of the dorsal intercarpal reconstruction at 70-degree flexion was 0.8 mm. During flexion, the dorsal intercarpal reconstruction showed no ligament tears or failure of the bone anchor. The mean elongation of the dorsal intercarpal complex was 3.9 mm at 70 degrees. During subsequent repeated flexion, four sutures to connect the dorsal intercarpal complex to the surrounding tissue loosened between 55 and 60 degrees.Conclusions These findings suggest that capsulodesis can safely withstand flexion of the wrist until 50 degrees.Clinical Relevance Clinicians should consider the opportunity to start early with controlled active motion.Level of Evidence Not applicable.
Keywords: biomechanics; capsulodesis; scapholunate interosseous ligament (SLIL); SL-ligament